2023
DOI: 10.1007/s00787-022-02135-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of universal, school based, interventions on help seeking in children and young people: a systematic literature review

Abstract: Reviews into universal interventions to improve help seeking in young people focus on specific concepts, such as behaviour, do not differentiate between interpersonal and intrapersonal help seeking, and often report on statistical significance, rather than effect size. The aim of this review was to address the gaps highlighted above, to investigate the impact of universal, school-based interventions on help-seeking in children and young people, as well as to explore longer term impact. Four databases were sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…A recent systematic review of RCTs showed that these programs increase mental health literacy and reduce stigma, although there is a lack of evidence on whether these effects per sist over the long term 337 . Whether they increase helpseeking be haviour remains unclear 338 .…”
Section: School-based Mental Health Programsmentioning
confidence: 99%
“…A recent systematic review of RCTs showed that these programs increase mental health literacy and reduce stigma, although there is a lack of evidence on whether these effects per sist over the long term 337 . Whether they increase helpseeking be haviour remains unclear 338 .…”
Section: School-based Mental Health Programsmentioning
confidence: 99%
“…For instance, discrimination and bullying victimisation are two risk factors at the community level that undermine adolescents' emotional, social and mental well-being (Priest, King, B ecares, & Kavanagh, 2016). While there is increasing recognition of the roles of schools in monitoring and supporting adolescents' mental health and well-being through both whole-population and targeted-population interventions (Hayes et al, 2023), there is also a need for family engagement and community involvement as well as coherent policy responses across educational, health and social systems. In Australia, the Be You programme (Beyond Blue, 2023) is a good example that helps schools work together with families and communities to take care of adolescents' mental health needs by creating a positive and resilient environment and improving educators' mental health knowledge and skills.…”
Section: Implications For Future Research and Practicementioning
confidence: 99%
“…In the field of help‐seeking interventions, there are mainly two approaches: a whole‐population approach that is aimed at the general population (Velasco et al., 2020) and a target‐population approach that is aimed at people with or at risk of mental health problems (Gulliver, Griffiths, Christensen, & Brewer, 2012). Findings from previous systematic reviews showed that the target‐population approach might be more effective than the whole‐population approach and interventions to promote formal help‐seeking might be more effective than informal help‐seeking across the life span (Gulliver et al., 2012; Hayes et al., 2023; Xu et al., 2018). This suggests differing factors may act on help‐seeking by populations of interest and sources of help‐seeking.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusive education system, according to these studies, results in a positive sense of self and self‐worth for all children, whether or not they experience disability, due to a higher level of interaction when compared with a segregated system (Kielblock & Woodcock, 2023; She & Yao, 2022; Sirikulchayanonta et al, 2022). Children who participate in inclusive education have also been found to be more independent (Hayes et al, 2023; Mickelsson, 2023).…”
Section: Introductionmentioning
confidence: 99%